Dante Gabriel Rossetti and Music: Introduction. (17th February 2022) - Allis, Michael
Abstract: This introduction provides an overview of this Roundtable on Dante Gabriel Rossetti and music. In addition to situating the issue in relation to previous studies of Rossetti and music, poetry and art, and suggesting some topics for future research, a summary of each article is provided, outlining its content and significance.